Dealing with disasters: perspectives from eco-cosmologies - Riboli, Diana; Stewart, Pamela J.; Strathern, Andrew; Torri, Davide (Springer International Publishing, 2021)
Chapter 1. Introduction, Diana Riboli and Davide Torri -- Chapter 2. “The War Has Just Begun.” Nature’s Fury against Neocolonial ‘Spirit/s’: Shamanic Perceptions of Natural Disasters in Comparative Perspective, Diana Riboli -- Chapter 3. The Spirits of Extractivism: Non-human Meddling, Shamanic Diplomacy and Cosmo-political Strategy among the Urarina (Peruvian Amazon), Emanuele Fabiano -- Chapter 4. Batek Cosmopolitics in the Early 21st Century, Ivan Tracey -- Chapter 5. Jinn Pinn Dance in the Floods: Perceptions of Flood Disasters among the Kalasha of Pakistan, Taj Khan Kalash -- Chapter 6. Eco-Cosmologies: Renewable Energy , Pamela J. Stewart and Andrew J. Strathern -- Chapter 7. The Earth and the Tree in Alekh Shamanism in Koraput/ Odisha, Lidia Guzy -- Chapter 8. Sacred, Alive, Dangerous and Endangered: Humans, Non-humans and Landscape in the Himalayas, Davide Torri -- Chapter 9. Shamanism, Magic and Indigenous Ontologies: Eco-critical Perspectives on Environmental Changes in India, Stefano Beggiora -- Chapter 10. Unblocking the Blockage between Earth and Heaven: Shamanic Space for Cultural Intimacy in China, Naran Bilik -- Chapter 11. Burying gold, digging the past: remembering Ma Bufang regime in Qinghai (PRC), Valentina Punzi.